Analisis kelayakan usaha budidaya rumput laut (Kappaphycus alvarezii) menggunakan alat horizontal net (Studi kasus di Kelurahan Katobengke Kecamatan Betoambari Kota Baubau) - Sima, Nur; Kasim, Ma'ruf; Nurdiana A (Universitas Halu Oleo, 2021)
Kappaphycus alvarezii is a seaweed species that has been widely cultivated in Indonesia include in Southeast Sulawesi using long line method. Horizontal net is a promising cultivation method for K. alvarezii to protect the cultured seaweed from ephyphytes and herbivores that usually occur when using long line. This innovative culture method is considered cheap and labor extensive although the economoc feasibilty is still unknown. This research was conducted in Katobengke Village, Betoambari District, Baubau City. The method used in this research was a case study using horisontal net farmes in the village. The data obtained were analyzed using Net Present Value (NPV), Revenue Cost Ratio (R/C), Internal Rate Of Return (IRR) and Payback Period (PBP). The results of the feasibility analysis of the NPV positive 342.031.587, with an interest rate of 12,5%, the value of R/C Ratio> 1 (1,28), IRR 25% and PBP for 3.9 years were obtained. The present study indicated that the cultivation of seaweed using Horizontal Net in Katobengke Village is feasible to be further developed.